A NEW APPROACH TO THE RULE-BASED SYSTEMS DESIGN AND IMPLEMENTATION PROCESS - Nalepa, Grzegorz J. (Computer Science, 2013)
The paper discusses selected problems encountered in practical rule-based systems (RBS) design and implementation. To solve them XTT, a new visual knowledge representation is introduced. Then a complete, integrated RBS design, implementation and analysis methodology is presented. This methodology is supported by a visual CASE tool called Mirella.The main goal is to move the design procedure to a more abstract, logical level, where knowledge specification is based on use of abstract rule representation. The design specification is automatically translated into Prolog code, so the designer can focus on logical specification of safety and reliability. On the other hand, system formal aspects are automatically verified on-line during the design, so that its verifiable characteristics are preserved.